Cellular Analysis and Chemotherapeutic Potential of a Bi-Functionalized Halloysite Nanotube - Yangyang Luo; Ahmed Humayun; Teresa A. Murray; Benjamin S. Kemp; Antwine McFarland; Xuan Liu; David K. Mills (Pharmaceutics, 2020)
The surface of halloysite nanotubes (HNTs) was bifunctionalized with two ligands—folic acid and a fluorochrome. In tandem, this combination should selectively target cancer cells and provide a means for imaging the nanoparticle. Modified bi-functionalized HNTs (bi-HNTs) were then doped with the anti-cancer drug methotrexate. bi-HNTs were characterized and subjected to in vitro tests to assess cellular growth and changes in cellular behavior in three cell lines—colon cancer, osteosarcoma, and a pre-osteoblast cell line (MC3T3-E1). Cell viability, proliferation, and cell uptake efficiency were assessed. The bi-HNTs showed cytocompatibility at a wide range of concentrations. Compared with regular-sized HNTs, reduced HNTs (~6 microns) were taken up by cells in more significant amounts, but increased cytotoxicity lead to apoptosis. Multi-photon images confirmed the intracellular location of bi-HNTs, and the method of cell entry was mainly through caveolae-mediated endocytosis. The bi-HNTs showed a high drug loading efficiency with methotrexate and a prolonged period of release. Most importantly, bi-HNTs were designed as a drug carrier to target cancer cells specifically, and imaging data shows that non-cancerous cells were unaffected after exposure to MTX-doped bi-HNTs. All data provide support for our nanoparticle design as a mechanism to selectively target cancer cells and significantly reduce the side-effects caused by off-targeting of anti-cancer drugs.